Dynamics of Industry Growth - Sengupta, Jati.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Economic growth of a country depends on its industries. The focus of modern growth theory is basically macroeconomics, although neoclassical models use competitive markets and the optimization behavior of households and firms in general equilibrium framework. The emphasis here is on industry growth, where the microfoundations of industry are analyzed in terms of economic efficiency. The various linkages which link firm growth with the industry growth are discerned here under various market structures both competitive and monopolistic. The role of information in facilitating market signals and allowing the adoption of new processes has been especially emphasized in this volume. Many issues of market failure and the suboptimality of competitive equilibria are due to incomplete and imperfect information structures and we need a comprehensive theory of information structures underlying the process of industry growth and its dynamics. This book will be of interest to economists studying economic and industry growth and innovation.
1.Theory of Industry Growth -- 2. A Pareto Model of Efficiency Dynamics -- 3. Market Dynamics and Growth -- 4. Market Rivalry and Interdependence -- 5. Technology and Innovations -- 6. Industry Evolution Mechanisms -- 7. Information and Efficiency.
Keywords: Economics; Endogenous growth (Economics).; Economics/Management Science; Economic Growth; Economic Theory; Political Science, general